ePoster: Hotel.CO / Siti Nur Athirah Mohd Asri, Amirah Raihanah Azmi, Noorfazirayu MdHanapi and Alya Syara Mohd Zin - Mohd Asri, Siti Nur Athirah; Azmi, Amirah Raihanah; Md Hanapi, Noorfazirayu; Mohd Zin, Alya Syara (2022)
After the covid-19 pandemic, many people wanted to travel everywhere. therefore, hospitality services are much needed. In general, the best hotel service will be the choice of travellers. as we know, previously the service to open the hotel room door only used the card provided by the hotel management. therefore, we will convert the card to one application.